A study of Malaysian national unit trust funds performance: case study of Amanah Saham National Berhad (ASNB) / Ismail Upia - Upia, Ismail (2009)
This paper seeks to focus on the return and risk of ASNB unit trust over the period since each fund started operating which is between 1990 until 2008. Four types fund of ASNB which is ASD, ASW2020, ASM and ASB unit trust have been randomly selected from ten type’s fund of unit trust that managed and offered by ASNB. The market benchmark use is KLCI Second Board. The researcher will investigate the ASNB unit trusts average return determine the total risk of ASNB, the relationship of ASNB unit trust return with KLCI Second Board return and the relationship of ASNB unit trusts risk with the KLCI Second Board risk. This paper use the annual total return, average return, standard deviation, coefficient of variation formula methods and Statistical Package for Social Sciences (SPPS) version 17.0 software to achieve the research objectives. The finding shows that the KLCI Second Board has the negative average yearly return. ASB shows the highest average yearly return followed by ASD, ASW2020 and ASM. The total risk that based on the value of standard deviation shows the highest total risk was ASD, followed by ASM, ASB and ASW2020. While Coefficient of variation shows that ASW2020 has the better risk-return tradeoff, followed by ASB, ASM and ASD.